A Network Analysis of Sectoral Accounts : Identifying Sectoral Interlinkages in G-4 Economies - Antoun de Almeida, Luiza (IMF Working Papers; Working Paper ;, 2015)
The recent financial crisis highlighted that balance sheet exposures can be a major shock transmission channel. Using sectoral accounts data in combination with data from the Coordinated Portfolio Investment Survey, International Investment Position, and BIS this paper estimates bilateral exposures between financial and non-financial sectors in three different financial instruments within and across G-4 economies (Euro Area, Japan, U.K. and U.S.). The generated financial networks represent a powerful tool for assessing financial stability, as they allow for the identification of systemically important sectors. The analysis suggests that after the financial crisis bilateral exposures in debt securities have increased, while exposures in loans and equities have declined. Shock simulations reveal that the vulnerability of the financial sector to the government sector has increased considerably since the outbreak of the financial crisis.